THERMAL COMFORT ANALYSIS IN OLDER ADULT HOUSING (CASE STUDY: LAWANG DISTRICT, MALANG) - Pakiding, Hana Ardina Putri; Ramadhani, Ledy Fitra; Pratiwi, Magvira Ardhia; Almadina, Alif Faricha; Jannah, Annissa 'Ul (Border: Jurnal Arsitektur, 2025)
Thermal comfort is crucial in building design because it can affect the occupants’ health, productivity, and well-being. For older adults, thermal comfort becomes critical, as aging can decrease their physiological ability to adapt to the environment temperature changes. Using field measurement and questionnaire survey, this research assessed the thermal comfort of older adult occupants in a naturally ventilated housing in Lawang District, Malang, Indonesia. Adaptive Comfort Model (ACM) was used to analyze thermal sensation (TSV), thermal acceptability (TA), and thermal preference (TP), with utilizing a psychometric chart. The result of the study indicates that climate-responsive and naturally ventilated housing can sustain acceptable thermal condition for older adult occupants, highlighting the importance of adaptive design strategies to enhance comfort and support healthy aging in tropical highland environment.